PRODUCTION PERFORMANCE EVALUATION OF D-LINE THREE STRAINS GRAND PARENT STOCK OF BROILER CHICKEN IN INDONESIA - Rosikin, Rosikin; Afnan, Rudi; Darwati, Sri; Muladno, Muladno (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
Production performance research was carried out on three Grand Parent Stock (GPS) broiler strains, namely Indian River, Ross and Cobb. The data was obtained from the results of production performance audits of broiler GPS breeders during the laying period of 25 – 65 weeks. Variables measured include laying lifeability, egg/hen house production, rate peak production/hen house, hatching egg/hen house production, fertility, hatchibilty, and saleable chick/henhouse. Data were analyzed quantitatively using t-test, analysis of variance (Anova) and Duncan. This study showed that the Indian river strain had higher production characteristics in terms of vitality, egg production, peak production, hatching egg production, and saleable chicks. Ross strains have higher production characteristics at rates of peak production, fertility, hatchability, and saleable chicks. The cobb strain has the lowest production performance compared to the other strains. Comparison between the strains and the principle standard shows that the actual hatchability and saleable chicks were lower than the standard in the Indian Rivers strain. The Ross strain had an actual value greater than the standard for fertility, hatchability and saleable chicks. Whereas the actual values for the Cobb strain for viability, egg production, peak production, hatching egg production, and saleable chicks were lower than the standard.